Obstructive Sleep Apnea Worsens Progression-Free and Overall Survival in Human Metastatic Colorectal Carcinoma - Lacedonia, Donato (J Oncol, 2021)
Sleep disorders have emerged as highly prevalent conditions, and along with improved understanding of such disorders, increased attention has gained the evidence that perturbation in sleep architecture and continuity may initiate, exacerbate, or modulate the phenotypic expression of multiple diseases including cancer. Furthermore, obstructive sleep apnea (OSA) has recently been implicated in increased incidence and more adverse prognosis of cancer in humans. This study was designed to confirm the high prevalence of OSA in human malignancies and assess its prognostic relevance in metastatic colorectal carcinomas (mCRCs). A prospective cohort of 52 subjects, affected by solid histologically confirmed metastatic malignancies, was analyzed, and among them, 29 mCRCs were studied for the prognostic role of OSA. OSA was diagnosed in 34.6% (18/52) of patients with a statistically significant difference in apnea-hyponea index between OSA and non-OSA subgroups (14.2 ± 12.2 vs. 2.1 ± 1.5, p < 0.01). Consistently, OSA was diagnosed in 34.5% (10/29) of mCRCs with lower rates of first-line therapy disease control in OSA compared to non-OSA patients (60% in OSA vs. 94.7% in non-OSA, p=0.03). Of note, progression-free and overall survival rates were significantly shorter in OSA (respectively, 9 and 22 months) compared non-OSA (20 and 40 months) mCRC patients (HR = 2.63; 95% CI 0.88–7.84, p=0.01 for PFS; HR = 3.93; 95% CI 1.13–13.73, p < 0.001 for OS). Finally, the multivariate analysis showed that OSA is an independent prognostic factor for PFS (p=0.0076) and OS (p=0.0017) in this cohort. Altogether, these data suggest that OSA is a potential clinical marker predictor of poor prognosis in patients with mCRC.